Some aspects regarding the activity of Bishop Nicodim Munteanu in Bessarabia (1918-1919) (Confluenţe Bibliologice, 2022)
The present research is about the activity of Bishop Nicodim Munteanu in Bessarabia (1918-1919), the future Patriarch of the Romanian Orthodox Church, who remains an emblematic ﬁgure of the Romanian Church and culture of all times, thanks to his insistence on performing the ﬁrst acts of ecclesiastical, administrative and Romanian uniﬁcation of the eparchial Chancellery and theological schools in Bessarabia. His activity in Bessarabia represents a right model to follow for all our hierarchs today, from a pastoral, household and administrative point of view. Keywords: Bishop Nicodim Munteanu, Romanian Orthodox Church, Bessarabian Church.
Keywords: Romanian Orthodox Church; Bessarabian Church